Al-doped NaNi1/3Mn1/3Fe1/3O2 for high performance of sodium ion batteries - Ma, Anxia; Yin, Zhoulan; Wang, Jiexi; Wang, Zhixing; Guo, Huajun; Yan, Guochun (Ionics, 2020)
Herein, we report a series of O3-type Na(Ni 1/3 Mn 1/3 Fe 1/3 ) 1-x Al x O 2 ( x = 0, 0.03, 0.05, 0.07) oxides as sodium-ion battery cathode materials synthesized via spray pyrolysis method. The structure, morphology, and electrochemical performance of Na(Ni 1/3 Mn 1/3 Fe 1/3 ) 1-x Al x O 2 ( x = 0, 0.03, 0.05, 0.07) are characterized by XRD, SEM, CV, and galvanostatic charge and discharge tests, respectively. Na(Ni 1/3 Mn 1/3 Fe 1/3 ) 0.95 Al 0.05 O 2 delivers an initial discharge capacity of 145.4 mAh g −1 at 0.1 C and exhibits a favorable reversible capacity about 128.4 mAh g −1 after 80 cycles at 0.2 C, with the capacity retention of 77.5% at the voltage range of 2.0 to 4.2 V. XPS analysis reveals that Al-doping could alleviate the Jahn-Teller effect caused by Mn 3+ and enhance the structural stability of layered oxides. The results confirm that a small quantity of (5 at. %) Al-doping improves the structural stability of the material, therefore leading to the excellent electrochemical performance.